An Exploratory Study of Online Job Portal Data of the ICT Sector in Bangladesh: Analysis, Recommendations and Preliminary Implications for ICT Curriculum Reform - Sheikh Saifur Rahman Jony; Tsuyoshi Kano; Ryotaro Hayashi; Norihiko Matsuda; M. Sohel Rahman (Education Sciences, 2022)
Many countries wish to achieve digital transformation, especially during the COVID-19 pandemic. The digital skills demand is changing fast. The time-series online job portal data for the ICT industry in Bangladesh provides an opportunity to analyze high demand job titles and skills over time. These time-series data address the question of the speed of changes in job titles and skills and responsiveness of computer science and engineering (CSE) curricula. This study gathers online job portal data of the ICT industry in Bangladesh from 2016 to 2021. Natural language processing is used to group similar skills and job titles following the O*NET Online taxonomy. In addition to the descriptive statistics, the statistical significance test and correlation analysis are conducted. The analysis could identify high demand ICT job titles (Software Developers, Computer System Engineers/Architects, Web Developers, Project Management Specialists) and skills (API, Database, JavaScript) but Computer System Engineer/Architect job titles and API skills are increasing fast. The shift from networking to JavaScript and UI Design is also noteworthy after COVID-19. The preliminary curricula analysis suggests the responsiveness of the CSE program, but online job portal data analysis might provide opportunities for developing unique CSE specialization, courses and curricula.